Pengembangan Motivasi dan Kapasitas Remaja Masjid di Masa Pandemi Covid-19 Melalui Pelatihan Dakwah Digital (Studi Kasus pada Remaja Mushola Baiturrahim Taman Sidoarjo) - Wulandari, Sri Dewi; Maisyaroh, Dewi Syafa Dinabilla (Proceedings of Annual Conference on Community Engagement, 2022)
Remaja Mushola Baiturrahim (Remusbara) experienced obstacles in carrying out da’wah through face to face during the pandemic. This has an impact on decreasing the level of activeness of the management in carrying out da’wah activities in the mosque youth organization. The implementation is carried out by providing assistance to generate organizational motivation through activities they are interested in, namely digital da’wah training in the form of creating da’wah content on social media and da’wah videography. At that time the youth were motivated to be active in Remusbara’s da’wah activities because the activities were very useful and fun. The results of the mentoring are in the form of capacity building for digital da’wah and increased motivation marked by a willingness to reactivate weekly activities in the form of learning the Qur’an for children.